Intrinsic Values and Human Rights: Corporate Duties Depend on Industry Values. Issue 2 (13th June 2022) - Donaldson, Thomas
Abstract: Drawing on the work of Donaldson and Walsh, this article explains why for-profit companies in industries denominated by intrinsic values such as health, education and justice, have heavier responsibilities when it comes to honouring the human rights reflected in their industry identity. Optimized collective value, the overarching aim of any system of business, is defined in terms of the satisfaction of intrinsic values, a definition that gives special meaning to firms operating in industries themselves defined in terms of intrinsic values. Nor are such companies' responsibilities to human rights, such as the right to healthcare, conveniently reducible to the 'enlightened' pursuit of profit. For example, a pharmaceutical company such as Pfizer or Moderna may be required to make its COVID-19 vaccine more accessible to COVID-19 victims in developing countries at the expense of optimizing profits over the long run. Such companies have a special and mandatory correlative duty to honour the right to healthcare that derives from their corporate constitutional purpose.